Matériaux pour une sociologie du travail des agents de la formation - Cédric Frétigné (Presses universitaires de la Méditerranée, 2011)
What is new or different in a perspective of sociology of work applied to vocational training professions ? Can this emergency research practise provide a best account of what adult education signifies ? In a first part, the article points that the sociology of professional groups, a largely dominant perspective, clearly disregards the question of vocational training professions work. In the second part, the benefits of some researches (about vocational training professions) led in sociology of work are showed. It appears necessary to examine the practices and to replace them inside of their social configurations. After, the text purposes a research program about this sociological perspective applied to vocational training professions. In particular, empirical investigations are encouraged. The conclusion synthesizes the principal gains of this orientation.